Mind Mapping Based Learning Model in Science Learning - Eka Fitria, Tazha; Rahmadani, Dea; Zaturrahmi, Zaturrahmi (Al-Khazini: Jurnal Pendidikan Fisika, 2025)
This study aims to analyze the use of mind mapping in learning, which includes: (1) the problems that lead to the utilization of mind mapping in learning, and (2) the variables influenced by the use of mind mapping in learning. The research method employed is a literature review with a sample of 10 articles. Data collection was carried out by gathering relevant scientific articles related to mind mapping and then analyzing them. The results of this study show that the main problem affecting the use of mind mapping in learning is the inadequacy of the methods applied to the subject matter being studied. Furthermore, the variables most influenced by the use of mind mapping are students’ learning outcomes and academic achievement.